Simulation and experimental design of adaptive-based maximum power point tracking methods for photovoltaic systems - Srinivasarao, P.; Peddakapu, K.; M. R., Mohamed; Deepika, K.K.; Sudhakar, K. (Elsevier, 2020)
This paper presents a filter-based adaptive fuzzy proportional integral derivative (FPIDN) controller for photovoltaic (PV) systems. The proposed maximum power point tracking (MPPT) method is implemented in two blocks. The first block represents by an adaptive calculation block; to produce a reference voltage for every maximum power point (MPP), whereas the second is the FPIDN controller; utilized to manage duty cycle of the PWM converter. The effectiveness of the proposed MPPT has been evaluated to different MPPT methods. The efficiency of the proposed MPPT recorded at 99.45% and 99.72% with MPP capture time clocks at 0.048s, outperforms the benchmarked traditional MPPT methods under diverse irradiance and temperature conditions.